Children’s Political Participation in the Digital Publich Sphere: An Analysis of Normative Boundaries in Politics A Review of Fiqh Siyasah - Zaqiaty Salma; Heru Permana Putra (Program Studi Hukum Tata Negara, 2026)
This article analyzes forms of children’s participation in the public sphere from the perspectives of legal and political jurisprudence. This is a qualitative study involving qualitative data analysis based on field research, utilizing descriptive qualitative data analysis techniques. The research findings reveal four forms of children’s political participation in public spaces, including Expressive Participation (Opinions and Support). This is evident when children express political views on social media, such as by liking, commenting on, or sharing political content, as well as following the accounts of political figures or parties. Second, Symbolic Participation, which can be seen occasionally appearing in campaign photos/videos on social media, using political paraphernalia (T-shirts, flags) in digital content, and being used as an icon or symbol of support. Additionally, Digital Campaign Participation involves creating campaign content (TikTok, Instagram, etc.), helping to spread specific political messages, and becoming part of a digital team (informally). Based on research, the legal status of involving children in political campaign activities under positive law in Indonesia is implicitly regulated in Article 280(2) of Law No. 7 of 2017 on Elections and Article 1(1) of the Child Protection Law; it is prohibited if the child is under 17 years of age. As for fiqh siyasah, the various forms of involving children in elections in the digital space violate the principle of maslahah (there is no m